Analisis Usahatani Ubi Kayu Varietas Gajah (Studi Kasus di Kelompok Tani-Ternak Kerti Winangun, Desa Bukti, Kecamatan Kubutambahan, Kabupaten Buleleng) - MARDIKA, I NENGAH; RANTAU, I KETUT; WIJAYANTI, PUTU UDAYANI (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism); Vol.6, No.2, April 2017, 2017)
Farming cassava analysis of Gajah varieties (Case study in farmer livestock group Kerti Winangun, Bukti Village, Kubutambahan Sub-District, Buleleng Regency) Cassava is one of crops that economically potential to be developed in order to meet food needs in addition to rice. Village of Bukti, Sub-District of Kubutambahan, is one of the cassava production centers in Buleleng, but the locally developed cassava waslower in its production and productivity. In order to improve the productivity and production of cassava, the Farmers Group of Kerti Winangun of Bukti Village have developed superior cassava varieties of Gajah. This study aimed to determine the revenue, R / C ratio, and the constraints of farming cassava varieties of Gajah by the Farmers Group of Kerti Winagun at Bukti Village. The choice of location was done purposively and to determine the respondents, it was conducted by census. The results of the research of farm cassava varietiesof Gajah in the planting season of 2015 shows that the production cost of Rp. 15,738,424.00, with the revenue amounting to Rp. 47,367,300.00, which generated revenues of Rp. 31,628,876.00 per hectare with R / C ratio of 3.00 means that farming is profitable or feasible to proceed. Technical constraints faced were limited cassava seeds, and the attack of white pest. Economic constraint was the lower price of potatoes soggy in the market. Climate constraint was the low rainfall. Farmers are advised to take advantage of cuttings of cassava of Gajah varieties of the previous harvest, to perform processing of crops so as to increase the sale value, as well as building ponds to collect rain water for watering plants that can be helpful in the dry season.
Keywords: farming; cassava; high yielding varieties of Gajah